Adolescent pain, anxiety, and depressive problems: a twin study of their co-occurrence and the relationship to substance use. Issue 3 (19th March 2022) - Scaini, Simona; Michelini, Giorgia; De Francesco, Stefano; Fagnani, Corrado; Medda, Emanuela; Stazi, Maria Antonietta; Battaglia, Marco
Abstract : Supplemental Digital Content is Available in the Text. The study indicates that several intertwined mechanisms, including genetic factors, can explain shared liability to common adolescent pain, anxiety, and depression problems. Abstract: Data on the etiological factors underlying the co-occurrence of common adolescent pain with anxiety and depression symptoms are very limited. Opioid prescriptions for adolescent pain problems are on the rise in North America and constitute a risk factor for diversion, misuse, and substance use. In this study, we aimed to investigate the phenotypic and etiological association among pain, depression, and anxiety and to test their link to substance use in adolescents. By taking advantage of the Italian National Twin Registry and of the relatively low incidence of opioid prescriptions in Italy, we applied multivariate modelling analyses to 748 Italian adolescent twins (374 pairs, mean age 16 ± 1.24 years). Twins' responses to the Achenbach Youth Self-Report questionnaire were used to build a composite adolescent pain index and to measure anxiety, depression, and substance use. All monozygotic within-pair correlations were higher than the dizygotic correlations, indicating genetic influences for adolescent pain, anxiety, and depressive problems. A common latent liability factor influenced by genetic and environmental elements shared among pain, depression, and anxiety provided the best fit to explain the co-occurrence of adolescent pain, anxiety, and depression problems. A common phenotypic factor capturing all 3 phenotypes was positively associated (β = 0.19, P < 0.001, confidence interval: 0.10-0.27) with substance use. These findings indicate that several intertwined mechanisms, including genetic factors, can explain a shared liability to common adolescent pain, anxiety, and depression problems. Their association with substance use remains traceable even in societies with relatively low prevalence of opioid prescriptions.